STRATEGI PEMBINAAN AHKLAK SISWA DI SMAN 1 PAGAR ALAM - Melky Sulyadi (UIN Fatmawati Sukarno Bengkulu, 2017)
Abstract: The results of this study indicate that: a) The principal maximizes system of managerial leadership by choosing people who are considered to be proficient in a certain position, which in the end with the coordination and structure of the planned policies principals will work well and the impact with the smooth process learning, b) Optimizing the spiritual activities of students, which Rohis and pembinanya cooperate with the council strives to provide an atmosphere that is religious in schools, added to that there are rules that created the municipality Pagar Alam that require students in schools along with civil servants sex women to wear the hijab, c) field of the student and the student council to cooperate in implementing the order in SMAN 1 Pagar Alam, to disseminate the new students about the discipline in high school and also to disseminate to the teachers, especially when there are regulations new. While the methods used in coaching ahklak conducted in SMAN 1 Pagar Alam is as follows: a) exemplary method, this is done by the whole board of teachers, school administration staff and existing components. For example, by coming on time, polite in speaking, greeting when meeting not smoking during the learning process, dressed in clean and tidy and participate in supervising the implementation of the discipline, b) Methods of punishment, which is done when students violate the existing rules such as coming late, not properly dressed, eating snacks when switching lesson. Punishment does not directly and immediately given, but starting first with the advice and warnings and penalties are applied priority to educate punishment. Method of good advice, which give teachers when the learning process, always motivate students to do good, give advice (advice) as well as services to students performing (that teachers do counseling), special teacher counseling, they tried to make approaches kinship is full of tenderness towards students with problems.